2019
DOI: 10.2147/ott.s199115
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of key genes and pathways in seminoma by bioinformatics analysis</p>

Abstract: Background: Seminoma accounts for the most part of cases of testicular germ cell tumor, which is the most common malignancy among males between ages 15 and 44 years. Understanding the molecular mechanism of tumorigenesis is important for better clinical diagnosis and treatment. Purpose: We performed bioinformatics analysis to better understand seminoma at the genetic level and to explore potential candidate genes or molecules for diagnosis, treatment, and prognosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…By combining 13 PRBs from different aspects, the linear regression model could reach an AUC value of 0.825. Thus, the strategy of screening PRBs from different aspects might better reflect the prognostic features of cancer patients as previous studies reported Chen Y. H. et al, 2019;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…By combining 13 PRBs from different aspects, the linear regression model could reach an AUC value of 0.825. Thus, the strategy of screening PRBs from different aspects might better reflect the prognostic features of cancer patients as previous studies reported Chen Y. H. et al, 2019;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We screened the DEGs between PCa samples with and without lymph node metastasis in TCGA cohort by the ‘limma’ R package. Adjust P ‐value < .05 and |logFC| ≥2 were set as the cut‐off criterion for a better accuracy and significance as described previously …”
Section: Methodsmentioning
confidence: 99%
“…The DEGs between samples with high and low proportions of M2-TAMs in TCGA cohort were analyzed using the “limma” R package. As described previously, adjusted P-value <0.05 and |logFC| ≥2 was set as the cut-off criterion for better accuracy and significance ( 19 , 20 ).…”
Section: Methodsmentioning
confidence: 99%